Relationship between institutional case volume and one-month survival among cases of paediatric out-of-hospital cardiac arrest. (April 2019) - Amagasa, Shunsuke; Kashiura, Masahiro; Moriya, Takashi; Uematsu, Satoko; Shimizu, Naoki; Sakurai, Atsushi; Kitamura, Nobuya; Tagami, Takashi; Takeda, Munekazu; Miyake, Yasufumi; ,
Abstract: Aim: To evaluate volume–outcome relationship in paediatric out-of-hospital cardiac arrest (OHCA). Methods: This post hoc analysis of the SOS-KANTO 2012 study included data of paediatric OHCA patients <18 years old who were transported to the 53 emergency hospitals in the Kanto region of Japan between January 2012 and March 2013. Based on the paediatric OHCA case volume, the higher one-third of institutions (more than 10 paediatric OHCA cases during the study period) were defined as high-volume centres, the middle one-third institutions (6–10 cases) were defined as middle-volume centres and the lower one-third of institutions (less than 6 cases) were defined as low-volume centres. The primary outcome measurement was survival at 1 month after cardiac arrest. Multivariate logistic regression analysis for 1-month survival and paediatric OHCA case volume were performed after adjusting for multiple propensity scores. To estimate the multiple propensity score, we fitted a multinomial logistic regression model, which fell into one of the three groups as patient demographics and prehospital factors. Results: Among the eligible 282 children, 112, 82 and 88 patients were transported to the low-volume (36 institutions), middle-volume (11 institutions) and high-volume (6 institutions) centres, respectively. Transport to a high-volume centre was significantly associated with a better 1-month survival after adjusting for multiple propensity score (adjusted odds ratio, 2.55; 95% confidence interval, 1.05–6.17). Conclusion: There may be a relationship between institutional case volume and survival outcomes in paediatric OHCA.